Perceived impact of epilepsy in teenagers and young adults: An international survey - Baker, Gus A.; Hargis, Eric; Hsih, Marshall Mo-Song; Mounfield, Hilary; Arzimanoglou, Alexis; Glauser, Tracy; Pellock, John; Lund, Susanne (Epilepsy & behavior, 2008)
The purpose of this study was to survey the impact of epilepsy and its treatment on the quality of life, development, and opportunities for children/teenagers with the condition. We asked three groups—children/teenagers, parents and caregivers, and health care professionals—to complete specifically designed questionnaires containing clinical and demographic information and perceptions of the impact of epilepsy and its treatment on aspects of daily living, including education and leisure. For health care professionals, the survey included questions on area of speciality and volume of children with epilepsy seen in their clinic. Questionnaires were translated into the local written language in each participating country. Prepaid envelopes were provided for return of completed questionnaires. Responses were analyzed by an independent data analysis company. Two hundred twelve young people with epilepsy and 507 parents or carers of children/teenagers from 16 different countries completed the questionnaire. The majority of children were over the age of 12 (74%) and attended mainstream schools (64%). Approximately two-thirds (65%) of the children/teenagers who responded reported that their seizures caused them to lose, on average, 7 school days per year. More than one-third of the children/teenagers who responded to the survey (36%) have kept their epilepsy a secret from other people at some time for fear of being treated differently and a belief that people should not know (47%). The majority (87%) of respondents were taking epilepsy medications. More than a third of the children/teenagers who responded had experienced side effects in some form or another, with weight change (49%), headaches (46%), dizziness (41%), and shaking (33%) most commonly reported. More than one-third of the children/teenagers expected the condition to hinder their lives in the future, with impact on employment opportunities (73%), traveling and exploring (37%), and education (36%) most commonly reported. This survey documents some of the real-life consequences of childhood epilepsy and highlights important challenges and issues faced by children/teenagers with epilepsy and their families. Although there are a number of limitations to this study relating to sample selection, ensuring that children are as free from seizures as possible and minimizing the side effects of treatment must be the primary goal of epilepsy management, but considering the wider implications of epilepsy and treatment is also important.